The current progress in the use of boron as a platform for novel antiviral drug design. (2nd December 2022) - Wang, Shuo; Ren, Yujie; Wang, Zhao; Jiang, Xiangyi; Xu, Shujing; Zhang, Xujie; Zhao, Shujie; Zalloum, Waleed A; Liu, Xinyong; Zhan, Peng
ABSTRACT: Introduction: Boron has attracted extensive interest due to several FDA-approved boron-containing drugs and other pharmacological agents in clinical trials. As a semimetal, it has peculiar biochemical characteristics which could be utilized in designing novel drugs against drug-resistant viruses. Emerging and reemerging viral pandemics are major threats to human health. Accordingly, we aim to comprehensively review the current status of antiviral boron-containing compounds. Areas covered: This review focuses on the utilization of boron to design molecules against viruses from two perspectives: (i) single boron atom-containing compounds acting on miscellaneous viral targets and (ii) boron clusters. The peculiar properties of antiviral boron-containing compounds and their diverse binding modes with viral targets are described in detail in this review. Expert opinion: Compounds bearing boronic acid can interact with viral targets by forming covalent or robust hydrogen bonds. This feature is valuable for combating resistant viruses. Furthermore, boron clusters can form dihydrogen bonds and bear features such as three-dimensional aromaticity, hydrophobicity, and biological stability. All these features demonstrated boron as a probable essential element with immense potential for drug design.